O que diz um nome?: reflexões sobre o colonialismo e o Estado-nação em Luanda - Sampaio, Luisa Tui Rodrigues (2021)
Names, an important theme for anthropology, present themselves as an interesting starting point for analysis. Following this assertion, this master thesis has as its main focus to show and mobilize names as enunciated from the context of Luanda. In order to understand the possibilities of connections opened by them, as well as what they show, the focus is on the associations made by people, but also present in streets and papers, between names and the context where they are present in a historical perspective, this context being Luanda or Angola as a whole. Thus, names are a way of elaborating colonial relations and the political context in which they are situated. They are also a way in which denunciations of the violence engendered by colonialism are expressed. By producing fixations, displacements, and connections, names show the layers of discourses that mark the colonial and postcolonial context. In this understanding, enunciations about colonialism and the nation-state are evident in the figure of the Popular Movement for the Liberation of Angola (MPLA) - the party that has been in government since independence in 1975. Thus, the argument presented is organized from a deepening debate about the names themselves and, later, in the description of what they show about the colonial presence in the Luanda region as well as about the MPLA's discourse and the idea of national history claimed by it. This master thesis is the result of the connections that the names allow us to make.